Transformasi Pengelolaan Keuangan UMKM Melalui Akuntansi Syariah Berbasis Digital yang Transparan - Nur Aziza; Sitti Hardianti; Ade Meilisyah; Masyhuri Masyhuri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Digital transformation has become an important strategy in improving the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the Industrial Revolution 4.0 era. The use of digital technology can increase efficiency, productivity, innovation, and expand market access. However, the implementation of digitalization in Indonesian MSMEs still faces several challenges, such as low digital literacy, limited capital, lack of competent human resources, and weak technological infrastructure.This study aims to examine the importance of digital transformation in MSME financial management based on transparency and accountability. Digital financial management helps make recording and reporting processes more effective, transparent, and accessible, thereby increasing customer and business partner trust. In addition, digital systems also support faster and more accurate business decision- making.The results show that digital transformation can improve operational efficiency and create transparent, accountable, and competitive financial governance for MSMEs. Therefore, government support, increased digital literacy, and stronger technological infrastructure are needed to accelerate MSME digitalization in Indonesia.